The Influence of Digital Marketing Strategy, Customer Orientation, and Trust on Customer Loyalty through Shopee Customer Satisfaction in Makassar City - Abbas , Muchlis; Ginoga, Verri; Muin, Asri Nur (Amkop Management Accounting Review (AMAR), 2025)
The rapid development of digital marketplaces encourages companies to focus not only on customer acquisition but also on building sustainable customer loyalty. Intense competition has made customer loyalty a strategic issue, particularly for e-commerce platforms like Shopee. This study aims to analyze the influence of digital marketing strategies, customer orientation, and trust on customer loyalty through customer satisfaction among Shopee users in Makassar City. This study used a quantitative approach with a survey method. Data were collected through questionnaires distributed to 211 Shopee user respondents in Makassar City, using a purposive sampling technique. Data analysis was conducted using Structural Equation Modeling (SEM). The results show that digital marketing strategies, customer orientation, and trust have a positive effect on customer satisfaction. Furthermore, customer satisfaction has a positive and significant effect on customer loyalty and acts as a mediating variable that strengthens the influence of the three independent variables on customer loyalty. These findings confirm that digital marketplace customer loyalty is not only formed through promotions, but primarily through customer orientation and trust, which can create sustainable customer satisfaction.